Cluster-based spectrum sensing scheme in heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Mohd. Ramli, Huda Adibah; Hassan Abdalla Hashim, Aisha; Islam, Shayla; Hashim, Wahidah; Badron, Khairayu (Springer International Publishing Switzerland, 2015)
In OFDM based Heterogeneous Networks (HetNet) deploying femtocells (HeNodeBs) causes’ inter-cell interference in uplink as well as downlink. Spectrum allocation is one of the technique as many researcher identified. However, using frequency reuse/ cognitive system for dynamic spectrum reallocation is also a challenging issues. Therefore, this paper focuses on unused spectrum sensing (SS) through proposing cluster-based spectrum sensing for OFDM based two-tier HetNets. The proposed SS scheme adopted the basic model of energy detector and compared with cooperative spectrum sensing scheme. In the proposed scheme, the energy detection model is extended in to multiple channel detection model. To detect spectrums from nearby macrocell (macro-eNodeB) HeNodeBs are grouped in to cluster. A cluster formation algorithm is also proposed in where, cluster head (CH) and signaling node (SN) will detect implies the multi-channel SS technique. The simulation results demonstrate that the proposed scheme can improve the spectrum detection with minimum error. The performance of the proposed scheme is evaluated in Monte Carlo simulation validate the scheme performance